Use of a Removable Vena Caval Filter for Prevention of Recurrent Embolism after Emergency Pulmonary Embolectomy: A Flexible Approach - Jansen, Erik W. (1989)
Intraluminal vena caval filters, inserted via the transvenous approach, are used often in the prevention of recurrent pulmonary embolism. Until lately, such filters have been unremovable. In a recent case, however, we treated a patient who experienced acute massive pulmonary embolism after having undergone an emergency right hemicolectomy. He underwent a successful emergency pulmonary embolectomy with the help of cardio-pulmonary bypass; to prevent recurrent embolism, we inserted a removable intracaval filter through the right atriotomy with an introducer set. On the 7th postoperative day, the absence of significant residual thrombi was confirmed by means of phlebography, and the caval filter was removed percutaneously via the femoral approach. Although the value of routine use of the filter in this application has yet to be established, we feel that it warrants further investigation because it relieves the surgeon, during an emergency procedure, of the need to decide quickly whether or not to place a filter. The question becomes one of whether or not to remove the filter, and that decision can await the results of proper postoperative diagnostic studies. (Texas Heart Institute Journal 1989; 16: 15-17)